Examining the Impact of Sleep Quality on Mental Health and Quality of Life among University Students - Dr. Nighat Gul; Tayaba Ehsan; Dr. Amara Gul (Research Journal of Psychology, 2025)
This study examines the impact of sleep quality on mental health and quality of life among (N = 250) university students. The finding revealed a high prevalence of sleep problems, which significantly influenced the various aspects of students' life quality and mental health. Three scales were utilized for data collection likewise sleeps quality scale, mental health and quality of life. The poor quality of sleep was associated with lower mental health and quality of life. Good sleep quality associated with better mental health and quality of life. In addition, the impaired quality of life across four key domains, Physical Health, Psychological Health, Social Relationships, Environment due to insufficient sleep led to lower students with poor sleep quality also reported more complaints about physical health and impaired daily functioning along with reduced social relationships and psychological health. These results underline the critical need for interventions to improve sleep quality to improve both mental health and the overall quality of life of university students.